Web accessibility investigation and identification of major issues of higher education websites with statistical measures: A case study of college websites - Abid Ismail; K.S. Kuppusamy (Journal of King Saud University: Computer and Information Sciences, 2022)
The World Wide Web Consortium (W3C) has provided the most important set of guidelines for web accessibility which is popularly known as Web Content Accessibility Guidelines (WCAG). The accessibility analysis of higher education websites becomes paramount important to make them inclusive considering the growing number of enrollments of persons with disabilities (PwDs) in higher education, in countries such as India. This paper presents the accessibility analysis of higher education websites with the case study of college websites (N=44) affiliated with the University of Kashmir and Cluster University Srinagar. The study has been carried out with two major accessibility evaluation tools called web accessibility test, denoted as TAW and the accessibility engine powering browser extensions called the accessibility engine, denoted as aXe. This paper lists the major accessibility barriers exposed by these sites in terms of metrics such as a number of problems, warnings and a status of success criteria violations. With respect to TAW tool, a number of problems observed were 2646, a large number of warnings to the scale of 15995 and the not reviewed items were 1356. With aXe tool, the total violations observed were 1951 and items needing review were 1733. Findings of the statistical analysis are also presented in this paper. This paper presents a roadmap of steps for making these websites inclusive and barrier-free for PwDs.